The Frontline of Revitationalization: Influences Impacting Aboriginal Helpers - Goodleaf, Suzy; Gabriel, Wanda (First Peoples Child & Family Review, 2009)
Over the past two decades Aboriginal people have been transforming family, community and national life. With a fierce determination a movement that motivates change to heal destructive colonial and abusive patterns that has been simmering. On the front line of this movement are our elders, healers, counselors, social workers, police, teachers and faith keepers. The challenges facing the front line workers are very personal and at times political. This article seeks to shed light on the challenges of those on the front line of revitalization. It is based on the authors' experiences and observations of Aboriginals professionals and para-professionals (helpers) who are employed in their home communities, and highlights the specific influences they often face on a daily basis.